Persuasive Communication Strategies of Religious Extension Workers in Maintaining Religious Tolerance Between Communities in Berastagi District - Azida Zaini Br Sembiring; Syawaluddin Nasution (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. The objective of this study is to examine the persuasive communication strategies employed by religious counselors in fostering religious tolerance among communities, as well as to identify the challenges they face and their efforts to overcome these challenges. This research employs a qualitative approach, utilising purposive sampling to select participants. Data were gathered through interviews, observations, and document analysis, and analysed by means of data reduction techniques. The findings indicate that religious counselors employ persuasive communication strategies, including psychodynamic approaches to enhance emotional engagement during counseling sessions, sociocultural strategies by aligning counseling activities with the cultural norms of the Karo community in Berastagi, and meaning construction strategies to deepen understanding of religious tolerance among the populace. However, counselors face challenges, including their own limitations, strong adherence to local customs and traditions among the community, and alignment with national regulations concerning inter-religious tolerance and real-life incidents. Religious counsellors have made efforts to educate the community about the nation's foundational principles and to foster positive relationships with local residents. It is recommended that future research explore novel communication strategies from diverse perspectives in order to enrich the repertoire of creative and effective communication activities in community counselling.Keywords: Persuasive, Religious Counselor, Tolerant of Religious Communities.Abstrak. Tujuan penelitian ini adalah untuk mengetahui strategi komunikasi persuasif penyuluh agama dalam menjaga toleransi beragama antar masyarakat, dan hambatan penyuluh serta upaya mengatasinya. Penelitian ini menggunakan pendekatan kualitatif dengan teknik purposive sampling untuk memilih responden. Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, dan dianalisis dengan melakukan reduksi data. Hasil penelitian menunjukkan bahwa penyuluh agama menggunakan strategi komunikasi persuasif berupa psikodinamika untuk meningkatkan keterlibatan emosional dalam penyuluhan, strategi sosiokultural dengan menyesuaikan kegiatan penyuluhan dengan budaya masyarakat Karo di Berastagi, serta strategi konstruksi makna untuk memberikan pemahaman mendalam mengenai toleransi beragama kepada masyarakat. Hambatan yang dihadapi penyuluh adalah keterbatasan para penyuluh agama sendiri, pegangan adat dan budaya masyarakat yang kuat, serta penyelarasan antara aturan negara terkait toleransi antar umat beragama dan kejadian di lapangan. Upaya yang dilakukan oleh penyuluh agama adalah memberikan pemahaman kepada masyarakat tentang empat pilar kebangsaan dan berusaha menjalin hubungan yang baik dengan masyarakat. Untuk penelitian mendatang, disarankan untuk mengeksplorasi strategi komunikasi baru dari berbagai sudut pandang guna memperkaya repertoar kegiatan komunikasi yang kreatif dan efektif dalam penyuluhan kepada masyarakat.Kata Kunci: Persuasif, Penyuluh Agama, Toleransi Masyarakat Beragama.